Authentic Assessment in Vocational High School: Teachers’ Perspectives, Practice and Challenges - Nur Fatinah, Farida; Hikmat, Mauly Halwat; Ratih, Koesoemo (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study explores how English teachers at vocational high schools understand and apply authentic assessment within the Kurikulum Merdeka framework. Using a descriptive qualitative approach, Data were analyzed using thematic analysis by identifying key patterns from semi-structured interviews with two teachers, then triangulated through passive classroom observations to validate and enrich the findings. The findings show that both teachers have a good understanding of authentic assessment and are able to apply it through meaningful and relevant learning activities. They use methods such as projects, presentations, and practical tasks that reflect real-world skills. However, the study also found several challenges, including limited facilities, low student motivation, and time management difficulties due to large class sizes. These factors make it harder to implement authentic assessment effectively. Despite these obstacles, both teachers showed strong enthusiasm for using authentic assessment and highlighted the need for more training and support from the school. The study concludes that while authentic assessment is very relevant for vocational English education, its success depends on adequate resources, supportive policies, and continuous professional development.